2012
DOI: 10.1038/modpathol.2011.175
|View full text |Cite
|
Sign up to set email alerts
|

PAX2-null secretory cell outgrowths in the oviduct and their relationship to pelvic serous cancer

Abstract: With the exception of germ-line mutations in ovarian cancer susceptibility genes, genetic predictors for women destined for ovarian serous cancer cannot be identified in advance of malignancy. We recently showed that benign secretory cell outgrowths (SCOUTs) in the oviduct are increased in frequency with concurrent serous cancer and typically lack PAX2 expression (PAX2-null). The present study examined the relationship of PAX2-null SCOUTs to high-grade serous cancers by comparing oviducts from women with benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 26 publications
3
53
1
12
Order By: Relevance
“…With this approach, the proposed link between SCOUT frequency (per 10 5 microns or 10 centimeters) and neoplasia is validated. [11][12][13] We found in addition, as would be expected, that the mean amount of perimeter needed to identify the first SCOUT was less in cases of serous cancer. Moreover, the distribution of SCOUTs appeared to be random, without clustering in particular tissue sections of the fallopian tube ( Figure 5).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…With this approach, the proposed link between SCOUT frequency (per 10 5 microns or 10 centimeters) and neoplasia is validated. [11][12][13] We found in addition, as would be expected, that the mean amount of perimeter needed to identify the first SCOUT was less in cases of serous cancer. Moreover, the distribution of SCOUTs appeared to be random, without clustering in particular tissue sections of the fallopian tube ( Figure 5).…”
Section: Discussionsupporting
confidence: 75%
“…13 Follow-up studies recognized the need to account for both the age of the subjects and number of cross-sections examined. 12,13 When this was done, an additional link to age and a less pronounced (albeit still significant) relationship to malignancy was observed. This study was designed to more critically evaluate this relationship and create a method by which the surface area of the fallopian tube could be ascertained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies have suggested an association between STIC and endometrioid neoplasia [16,20]. Moreover, we have identified an association, albeit unclear, between benign proliferations with a "clonal" appearance (stem cell outgrowths (SCOUTs)) in the tube -some with endometrioid histology -and HGSC [21,22]. Thus it is conceivable that a small but unique subset of women have a vulnerability to both endometrioid and serous cancer precursor pathways or that both pathways share some yet to be clarified biologic underpinning.…”
Section: Discussionmentioning
confidence: 63%